Respiratory effects of different recruitment maneuvers in acute respiratory distress syndrome - Constantin, Jean-Michel (BioMed Central, 2008)
INTRODUCTION: Alveolar derecruitment may occur during low tidal volume ventilation and may be prevented by recruitment maneuvers (RMs). The aim of this study was to compare two RMs in acute respiratory distress syndrome (ARDS) patients. METHODS: Nineteen patients with ARDS and protective ventilation were included in a randomized crossover study. Both RMs were applied in each patient, beginning with either continuous positive airway pressure (CPAP) with 40 cm H(2)O for 40 seconds or extended sigh (eSigh) consisting of a positive end-expiratory pressure maintained at 10 cm H(2)O above the lower inflection point of the pressure-volume curve for 15 minutes. Recruited volume, arterial partial pressure of oxygen/fraction of inspired oxygen (PaO(2)/FiO(2)), and hemodynamic parameters were recorded before (baseline) and 5 and 60 minutes after RM. All patients had a lung computed tomography (CT) scan before study inclusion. RESULTS: Before RM, PaO(2)/FiO(2 )was 151 ± 61 mm Hg. Both RMs increased oxygenation, but the increase in PaO(2)/FiO(2 )was significantly higher with eSigh than CPAP at 5 minutes (73% ± 25% versus 44% ± 28%; P < 0.001) and 60 minutes (68% ± 23% versus 35% ± 22%; P < 0.001). Only eSigh significantly increased recruited volume at 5 and 60 minutes (21% ± 22% and 21% ± 25%; P = 0.0003 and P = 0.001, respectively). The only difference between responders and non-responders was CT lung morphology. Eleven patients were considered as recruiters with eSigh (10 with diffuse loss of aeration) and 6 with CPAP (5 with diffuse loss of aeration). During CPAP, 2 patients needed interruption of RM due to a drop in systolic arterial pressure. CONCLUSION: Both RMs effectively increase oxygenation, but CPAP failed to increase recruited volume. When the lung is recruited with an eSigh adapted for each patient, alveolar recruitment and oxygenation are superior to those observed with CPAP.